A criteria-based progressive rehabilitation program for rectus femoris strain in a recreational soccer player: a case report - González-de-la-Flor, Ángel; García-Pérez-de-Sevilla, Guillermo (Frontiers in Bioengineering and Biotechnology, 2024)
The purpose of this study was to describe the criteria-based progressive rehabilitation program implemented on a recreational soccer player diagnosed with a grade 1 rectus femoris strain. A 33-year-old male injured the rectus femoris muscle. At the first physical examination, the patient showed a significant physical impairment due to important limitations of the active range of motion of the knee flexion, and the hip flexors strength.The rehabilitation program consisted of specific training of the rectus femoris, lumbopelvic stabilization, mobility exercises, and running technique exercises, for six weeks, divided into three phases. Each week, the patient performed four rehabilitation sessions, combined with cross-training (swimming), to maintain his cardiorespiratory capacity. The patient improved functionally and returned to play soccer six weeks after the injury without pain. Moreover, the patient passed the criteria of each phase at week 2 for phase 1, at week 4 for phase 2 and at week 6 for phase 3. This case study demonstrates that criteria of progression may control the return to sport timetable for recreational soccer players according of functional and clinical limitations throughout the entire treatment.